World history and geography - Spielvogel, Jackson J. (McGraw-Hill networks, 2018)
The world before modern times, prehistory-A.D. 1500 -- The Renaissance in Europe, 1350-1600 -- The Reformation in Europe, 1517-1600 -- The Age of Exploration, 1500-1800 -- Conflict and absolutism in Europe, 1550-1715 -- The Muslim empires, 1450-1800 -- The East Asian world, 1400-1800 -- The Enlightenment and revolutions, 1550-1800 -- The French Revolution and Napoleon, 1789-1815 -- Industrialization and nationalism, 1800-1870 -- Mass society and democracy, 1870-1914 -- The reach of imperialism, 1800-1914 -- Challenges and transitions in East Asia, 1800-1914 -- World War I and the Russian Revolution, 1914-1919 -- The West between the wars, 1919-1939 -- Nationalism around the world, 1919-1939 -- World War II and the Holocaust, 1939-1945 -- The Cold War, 1945-1989 -- Independence and nationalism in the developing world, 1945-1993 -- Life during the Cold War, 1945-1989 -- A new era begins, 1989-present -- Contemporary global issues, 1989-present